Transient aeroelasticity of structures subjected to thunderstorm outflows. (15th October 2021) - Brusco, Stefano; Solari, Giovanni
Highlights: A mathematical model to evaluate motion-induced forces on slender structures subjected to thunderstorm outflows is proposed. Time-varying aerodynamic damping matrix and aerodynamic stiffness matrix of the system are defined. Three levels of analysis are addressed, according to the characteristics of the wind event. The classical solution for synoptic winds is found as a particular case. Suitable wind fields compatible with single-point records are rebuilt and applied on two configuration of a structure, estimating the motion-induced forces. The effects of the transient aeroelasticity are analysed and critically commented. Motion-induced forces are evaluated on slender real structures. Abstract: Literature is rich about studies which concern the insurgence of instability of structural systems under the action of steady flows, which have led to well-consolidated methods to assess the structural safety with regard to aeroelastic phenomena induced by synoptic winds. On the other hand, there are no clear references regarding aeroelasticity induced by the effect of thunderstorm outflows, events characterised by irregular variations of the wind speed and direction in a limited duration of time, which prevent the furnishing of a long time interval for the structure and the fluid to synchronise. This paper, based under the hypothesis of applicability of the classic strip and quasi-steady theory, illustrates a mathematical model able to consider the aeroelastic effects of thunderstorm outflows into the dynamic response of slender structures, from which the methodology for synoptic winds may be found as a particular case. After defining three different levels of analysis, applications regarding the Endless Column by Constantin Brâncuși under the action of ten thunderstorm outflows are proposed, whose outcomes are critically analysed and commented.